The effect of human resource competence and accounting information system implementation on financial performance at PT. Perkebunan Nusantara IV Regional I: Pengaruh Kompetensi Sumber Daya Manusia Dan Penerapan Sistem Informasi Akuntansi Terhadap Kinerja Keuangan Di PT. Perkebunan Nusantara IV Regional I - Pratiwi, Deswita; Lubis, Irna Triannur; Siregar, Fhikry Ahmad Halomoan (Institute of Computer Science (IOCS), 2025)
The purpose of this study is to investigate and analyze the impact of human resource development and accounting information system on the financial performance of region I of PT. Nusantara Plantation IV.The research method used in this article is multiple regression analysis. The independent variables in this study are human resources competence and the use of accounting information systems, while the dependent variable is financial performance. The research population in this study consists of all employees in personal personnel. Perkebunan Nusantara IV Regional I, where purposive sampling method was used and 70 respondents were selected. The data type used is primary data. The results of this study prove that Human Resource Competence does not have a significant effect on financial performance because the t-count value is 0.713, with a t-table value of 1.99. Note that the t-count value (0.713) < t-table (1.99) with a probability or sig. of the human resource competency variable is 0.478 > 0.05. The accounting information system has a significant effect on financial performance because the t_count value is 9,963, with a t-table value of 1.99, note that the t-count value (9,963) > t-table (1.99) with a probability or sig. of the accounting information system variable is 0.00 < 0.05. Human Resource Competence and the Implementation of Accounting Information Systems simultaneously have a significant effect on financial performance.